Study on Postfrac Softening Mechanism of Deep Marine Shale Reservoir in South Sichuan Basin - Zhou Xiaojin; Duan Yonggang; He XiaoPing; Zeng Bo; Song Yi (Geofluids)
Shale softening is an important factor affecting fracturing effect. Through the Brinell hardness measurement of deep marine shale reservoir in South Sichuan Basin, the softening mechanism of shale after fracturing is explored. Through laboratory test, the key parameters of shale Brinell hardness measurement are proposed as follows: indenter size 5 mm, loading force 613 N, 1226 N, and 2452 N, and holding time>10 s. It is determined that the content of quartz and clay is the main factor controlling the Brinell hardness of dry shale samples, and the mineral composition, microstructure, and fluid system jointly affect the shale softening process. The results show that (1) the marine shale in the South Sichuan Basin softens obviously, with the Brinell hardness decrease by more than 50%, (2) microfracture propagation and clay hydration expansion accelerate the shale softening process, leading to the decreased porosity and the increased number of micro-pores, and (3) the softening process is different between middeep shale and deep shale, with the latter characterized by high initial hardness and low softening rate.